Strategic planning and its relationship to the administrative performance of the Iraqi Football Association - أ.د سلام حنتوش رشيد صفاء صاحب نايف (physical education and sport sciences college for women/ Baghdad University, 2021)
The aim of the current research is to build a scale for strategic planning for programs to prepare athletes for international tournaments through strategic analysis of the internal and external environment with one of the analysis models that are compatible with the Iraqi environment, as well as building a measure of the administrative, technical and investment performance of members of the Iraqi Football Association from their point of view and finding the relationship between strategic planning for preparation programs Athletes for international tournaments and technical performance of the Iraqi Football Association. Where the research sample was determined from (224) workers in the Iraqi sub-federations, committees and sports clubs participating in the Iraqi Football Association competitions at a rate of (69.13%) and in a random way. The main sample was divided into three samples based on the requirements of the study to form the pilot sample (24(Of the workers (10.71%), the sample building the scale (100) of the workers, the rate (44.64%), and the sample application of the measures (100) of the workers (44.64%). The researcher concluded that successful strategic planning for any sports institution must be Associated with the use of the analysis.